Satisfaction of People with Police Roadside Procedures- a Case Study - Gorenak, Vinko; Prevolčić, Marko (Promet - Traffic&Transportation, 2008)
In the theoretical part of this paper, the authors present criteriaby which the satisfaction of the public with police workcan be measured. The focus lies on those criteria that are significantfor police work in the community and for the reputationof the police as a state organ itself, which is co-responsible for(improving) security in the nation. The empirical part of thispaper is based on a study that included 120 residents from thearea of Slovenj Gradec police directorate. The interviewees hadto give their opinion on various questions or statements abouttheir satisfaction regarding police roadside procedures in thearea that they live in. Furthermore, the authors examined theextent to which the residents are willing to help police officers,how they evaluate their work, on what basis the residents shapetheir opinion and how they evaluate interpersonal competenciesof police officers. The results have shown that the satisfactionof residents with roadside police procedures in SlovenjGradec police directorate is relatively good since the majority ofanswers varies between 3 and 4 on a Likert scale ranging from 1to 5. Even though the evaluations are promising, the authorsconclude the paper with several recommendations.